Ureterosygmoidostomy-associated hypokalemia-induced quadriparesis and rhabdomyolysis - Berilgen, MS; Mungen, B; Yakinci, C; Bulut, S (Blackwell Publishing Asia, 2005)
[Abstract Not Available]
Keywords: hypokalemia; quadriparesis; rhabdomyolysis; ureterosygmoidostomy